Composition for battery electrode

By using polyamine cores and conductive carbon-based materials in the composition of the rechargeable battery pack electrode and connecting the polyester segments through ionic bonds, the problem of poor effect of the composition in the prior art in dispersing the conductive carbon-based materials is solved, and an electrode composition with low viscosity and high performance is achieved.

CN119563245APending Publication Date: 2025-03-04BYK CHEMIE GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380015083.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The compositions for rechargeable battery pack electrodes in the prior art are poor in dispersing conductive carbon-based materials, especially compositions with low viscosity are difficult to achieve.

Method used

Compositions containing polyamine cores and conductive carbon-based materials are employed, wherein the polyamine cores are prepared by reacting the polyamine with a compound having an epoxy group and connecting a plurality of polyester segments via ionic bonds, and the weight ratio of the polymer to the conductive carbon-based material is in the range of 70:100 to 3:100.

Benefits of technology

The composition with low viscosity is achieved, suitable for preparing electrodes for rechargeable battery packs, improving the dispersion effect of conductive carbon-based materials and enhancing the performance of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563245A_ABST
    Figure CN119563245A_ABST
Patent Text Reader

Abstract

The present invention relates to a composition comprising a) a polymer having i) a polyamine core comprising a plurality of amine groups and comprising a structure of formula (I) wherein R1 is H or part of the polyamine core, R2 is H or an organic group, R3 is H or an organic group, provided that at least one of R2 and R3 is H, ii) a plurality of polyester segments attached to the polyamine core via ionic bonds, and b) an electrically conductive carbon-based material, wherein the weight ratio of the polymer a) to the conductive carbon-based material b) in the composition of the invention is in the range of 70: 100 to 3: 100. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a composition comprising a polymer and an electrically conductive carbon-based material, to the use of the composition for preparing an electrode for a rechargeable battery, to a method for preparing a rechargeable battery electrode, to a battery electrode and to a rechargeable battery.

[0002] WO 2021 / 028519 A describes a dispersant comprising a polyester derived from a polylactone and an amine, which has an acid value of less than 15 mg KOH / g. The document also describes the use of the dispersant in a composition for a rechargeable lithium-ion battery electrode. It has been found that the dispersants described in this document do not always provide satisfactory results for dispersing conductive carbon-based materials.

[0003] US 9574121 B2 relates to a process for preparing amine adducts, wherein a polyamine component, a polyester component and an epoxide-functional component are reacted. The amine adducts are suitable as wetting agents and dispersants, in particular for coatings and plastics applications.

[0004] There remains a need for improved compositions for preparing electrodes for rechargeable batteries, particularly compositions comprising conductive carbon-based materials having low viscosity.

[0005] The present invention provides a composition comprising

[0006] a) a polymer having

[0007] i) a polyamine core comprising a plurality of amine groups and comprising a structure of formula (I)

[0008]

[0009] Where R 1 is part of the H or polyamine nucleus, R 2 is H or an organic group, R 3 is H or an organic group, provided that R 2 and R 3 At least one is H,

[0010] ii) a plurality of polyester segments connected via ionic bonds to a polyamine core, and

[0011] b) Conductive carbon-based materials,

[0012] The weight ratio of the polymer a) to the conductive carbon-based material b) in the composition of the present invention is in the range of 70:100 to 3:100.

[0013] As mentioned above, the polymer of the composition of the present invention comprises a polyamine core. Examples of suitable polyamine cores are aliphatic linear polyamines such as diethylenetriamine (DETA), triethylenetetramine (TETA), tetraethylenepentamine (TEPA), pentaethylenehexamine, hexaethyleneheptamine and higher homologues, general formula NH2-(C2H4NH) with n>5 n -Higher linear condensation products of -C2H4-NH2, dipropylenetriamine, (3-(2-aminoethyl)aminopropylamine, N,N-bis(3-aminopropyl)methylamine, tetramethyliminobispropylamine, N,N-dimethyldipropylenetriamine, bis-(3-dimethylaminopropyl)amine and N,N′-bis(3-aminopropyl)-ethylenediamine.

[0014] Suitably, the polyamine core is an organic polyamine compound containing an average of at least 2, preferably from 6 to 600, tertiary amino groups.

[0015] Tertiary amino groups generally lead to good adsorption on solid surfaces and have only a low tendency to cause adverse reactions. In addition, tertiary amino groups enable high molecular weight structures to be achieved while the viscosity remains relatively low.

[0016] Typically, branched aliphatic polyamines with primary, secondary and tertiary amino groups are used, in particular poly(C2-C4)-alkyleneamines. Particularly preferred polyamine cores are polyethyleneimines. Polyethyleneimines are commercially available, for example under the trade name Available from BASF or under the trade name Available from Nippon Shokubai. These are produced by known methods, for example, by polymerization of ethyleneimine.

[0017] Typically, in the polyamine core, the molar ratio of primary amino groups to secondary amino groups is in the range of 1:1 to 1:5. Typically, the molar ratio of primary amino groups to tertiary amino groups is in the range of 3:1 to 1:3.

[0018] In a typical embodiment, the polyamine core has a weight-average molecular weight in the range from 200 to 200,000, preferably from 250 to 40,000, particularly preferably from 300 to 25,000 g / mol.

[0019] Too low a molecular weight may result in weak adsorption on the solid surface, while too high a molecular weight may cause problems in manageability and solubility.

[0020] The weight average molecular weight of the polyamine core can be suitably determined using light scattering.

[0021] The polyamine core comprises a structure according to formula (I). The polyamine core with a structure according to formula (I) is suitably prepared by the reaction of a polyamine with a compound having at least one epoxy group. Preferably, the compound having at least one epoxy group has 3 to 25 carbon atoms. More preferably, the compound has 4 to 20 carbon atoms. Particularly preferably, an epoxide compound having one epoxy group per molecule is used.

[0022] Suitable compounds having at least one epoxy group are glycidyl ethers, glycidyl esters, epoxidized olefins, appropriately epoxidized α-olefins.

[0023] Preferred glycidyl ethers are glycidyl ethers with a C2 to C30 hydrocarbon group connected to an ether atom. The hydrocarbon group can be aliphatic (including alicyclic), aromatic, aromatic aliphatic, and it can be linear or branched, saturated or unsaturated. Preferably, the group is selected from C4 to C24 aliphatic groups and substituted or unsubstituted phenyl. Very preferably, the group is selected from saturated C6 to C18 aliphatic groups, such as C8 to C16 alkyl. Suitable examples are n-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, C8-C10 aliphatic glycidyl ether, C12-C14 aliphatic glycidyl ether, C13-C15-alkyl glycidyl ether, oleyl glycidyl ether, allyl glycidyl ether and cresyl glycidyl ether, p-tert-butylphenyl glycidyl ether, nonylphenyl glycidyl ether, phenyl glycidyl ether, naphthyl glycidyl ether. Preferred examples are 2-ethylhexyl glycidyl ether and C12-C14-aliphatic glycidyl ethers, and C13-C15-alkyl glycidyl ethers.

[0024] Preferred glycidyl esters are glycidyl esters having a C2 to C30 hydrocarbon group connected to the ester group. The hydrocarbon group may be aliphatic (including alicyclic), aromatic, aromatic aliphatic, and it may be linear or branched, saturated or unsaturated. Preferably, the group is selected from C4 to C24 aliphatic groups and substituted or unsubstituted phenyl. Very preferably, the group is selected from saturated C6 to C18 aliphatic groups, such as C8 to C16 alkyl.

[0025] Suitable examples are 2-ethylhexyl glycidyl ester and the glycidyl ester of neodecanoic acid.

[0026] Preferred epoxidized olefins are those based on alpha-olefins containing 4 to 30 carbon atoms. The hydrocarbyl group connected to the epoxy group can be aliphatic (including alicyclic), aromatic, aromatic aliphatic, and it can be linear or branched. Preferably, the group connected to the epoxy group is selected from C4 to C24 aliphatic groups and substituted or unsubstituted phenyl. Very preferably, the group is selected from saturated C6 to C18 aliphatic groups, such as C8 to C16 alkyl.

[0027] Suitable examples of epoxidized olefins are 1,2-hexene oxide, 1,2-epoxyoctane, 1,2-epoxynonane, 1,2-epoxyundecane, 1,2-epoxydodecane, 1,2-epoxyoctadecane, 4-methyl-1,2-epoxypentane, 1,2-epoxybutylene oxide, styrene oxide, butadiene monoxide, isoprene monoxide, cyclopentene oxide and 2-ethyl-1,2-epoxybutylene oxide.

[0028] Preferably, in formula (I), R 2 and R 3 The organic group is a hydrocarbon group or an organic group containing an ether group or an ester group. Due to the ring opening of the oxirane group during the reaction of polyethyleneimine with epoxide, R in formula (I) 2 and R 3 One of them is the hydrogen atom.

[0029] If the nitrogen atom of structure (I) is a secondary amine, R 1 is hydrogen. The secondary amine can be further modified with a compound having at least one epoxy group. In this case, the reaction process results in the conversion of the secondary amine into a tertiary amine, wherein R 1 yes

[0030]

[0031] In addition, the polyethyleneimine may contain non-terminal secondary amine groups. If such groups react with epoxy groups, polyethyleneimine of structure (I) is formed, wherein R 1 is part of polyethyleneimine. This means that R 1 Contains at least one repeating unit comprising a nitrogen atom and two CH2 groups.

[0032] In a preferred embodiment, the polyamine core is the reaction product of polyethyleneimine and at least one compound having at least one epoxy group, wherein the molar ratio of total amine groups of polyethyleneimine to epoxy groups from the compound having at least one epoxy group is between 100.0:30.0 and 100.0:0.3, preferably between 100.0:20.0 and 100.0:1.0, more preferably between 100.0:15.0 and 100.0:2.0, most preferably between 100.0:13.0 and 100.0:3.0, such as between 100.0:10.0 and 100.0:4.0.

[0033] In another preferred embodiment, the polyamine core is a reaction product of polyethyleneimine and at least one compound having at least one epoxy group, wherein the molar ratio of primary amine groups of polyethyleneimine to epoxy groups from the compound having at least one epoxy group is between 100.0:80.0 and 100.0:1.0, preferably between 100.0:50.0 and 100.0:3.0, more preferably between 100.0:40.0 and 100.0:6.0, most preferably between 100.0:35.0 and 100.0:8.0, such as between 100.0:30.0 and 100.0:10.0.

[0034] As mentioned above, the polymer comprises a plurality of polyester segments linked via ionic bonds to a polyamine core.

[0035] Suitable polyester segments can be produced by reacting dicarboxylic acids and their esterifiable derivatives, such as anhydrides, acid chlorides or dialkyl esters, such as dimethyl esters or diethyl esters, with diols and monofunctional carboxylic acids. If necessary, the formation of dihydroxy polyesters can be suppressed by using a corresponding stoichiometric amount of monofunctional carboxylic acids. The esterification can be carried out in bulk or by azeotropic esterification in the presence of an entrainer. Such condensation reactions are carried out, for example, at temperatures of about 50° C. to 250° C. Examples of dicarboxylic acids that can be used in this way are succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, sebacic acid, pimelic acid, phthalic acid or dimer fatty acids and their isomers, and their hydrogenation products. Examples of diols that can be used in this way are ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cis-1,2-cyclohexanedimethanol, trans-1,2-cyclohexanedimethanol and polyglycols based on ethylene glycol and / or propylene glycol. The corresponding monocarboxylic acids used as starting components preferably have 1 to 42 carbon atoms, in particular 4 to 18 carbon atoms, preferably 8 to 14 carbon atoms, and can be saturated or unsaturated, aliphatic or aromatic, linear, branched and / or cyclic. Examples of corresponding suitable monocarboxylic acids are stearic acid, isostearic acid, oleic acid, lauric acid and benzoic acid. Further suitable acids are tertiary monocarboxylic acids, also called Koch acids, such as 2,2-dimethylpentanoic acid, tert-nonanoic acid and neodecanoic acid. Koch acids of this type are also available as commercial products under the trade name TRICARBOXYLIC ACID. It is known by the names of hydroxyacids (Shell), Neo-acids (Exxon) or Cekanoic acids (Kuhlmann). Acids are named according to the total number of carbon atoms in the molecule. Suitable examples are Acids 5, 6, 9 and 10.

[0036] The polyester segment suitably contains at least 5, preferably from 6 to 70 ester groups.

[0037] In a further embodiment, the polyester segments additionally contain ether groups.

[0038] The polyester segments are connected to the polyamine core via ionic bonds. In order to form ionic bonds between the polyamine core and the polyester segments, the polyester segments suitably include carboxylic acid groups. The carboxylic acid groups of the polyester segments easily form salts with the amine groups present in the polyamine core, thereby connecting the polyamine core to the polyester segments via ionic bonds. In a preferred embodiment, the average number of the carboxylic acid groups of the polyester segments is in the range of 0.9 to 1.5. The carboxylic acid groups may exist as end groups or side groups. Terminal carboxylic acid groups are preferred.

[0039] Carboxyl acid functionality above 1.5 may cause crosslinking, which generally results in poor solubility, reduced compatibility, excessive viscosity, or insufficient compatibility.

[0040] Particularly suitable polyester segments are those obtainable by polycondensation of one or more optionally alkyl-substituted hydroxycarboxylic acids, such as ricinoleic acid or 12-hydroxystearic acid, and / or ring-opening polymerization of the corresponding lactones, such as propiolactone, valerolactone and caprolactone. It is therefore preferred that the polyester segments contain the formula -[-O-(CH2) n -C(=O)]-, wherein n is an integer in the range of 3 to 6. The lactone polymerization is carried out using known methods, initiated with, for example, p-toluenesulfonic acid or dibutyltin dilaurate at temperatures of about 50° C. to 200° C. Particularly preferred are polyesters based on ε-caprolactone, optionally in combination with δ-valerolactone.

[0041] Typically at least 50% by weight, preferably 70 to 100% by weight, of the polyester segments are linear, monocarboxyl-functional caprolactone polyesters.

[0042] The polyester segment suitably has a weight average molecular weight in the range of 500 to 10000 g / mol, preferably 800 to 8000 g / mol.

[0043] A weight average molecular weight of less than 500 or greater than 10,000 generally impairs general compatibility.

[0044] Number average molecular weight M n and weight average molecular weight M w It can be determined by gel permeation chromatography (GPC) according to DIN 55672 Part 3 [2016-03].

[0045] As mentioned above, the polyester segments of the polymer are linked to the polyamine core via ionic bonds. In a preferred embodiment, the polymer further comprises a polyester segment linked to the polyamine core via an amide group.

[0046] In an exemplary embodiment, 10 to 40% of the polyester segments are attached to the polyamine core via amide groups, and wherein 90 to 60% of the polyester segments are attached to the polyamine core via ionic bonds. The ratio of polyester segments attached to the polyamine core via ionic bonds to polyester segments attached to the polyamine core via amide bonds can be controlled by the reaction temperature of the polyamine core and the polyester segments. Lower temperatures in the range of 60 to 100° C. favor the formation of ionic bonds. Higher temperatures above 120° C. result in the formation of amide bonds in addition to ionic bonds.

[0047] The polymer used in the composition of the present invention is suitably prepared by a two-step process. In the first step, a polyamine is reacted with a compound having at least one epoxy group. Preferably, the polyamine has at least an amino group selected from primary and secondary amino groups. The compound having at least one epoxy group preferably has one epoxy group. The polyamine compound and the compound having at least one epoxy group are mixed and reacted at a temperature in the range of 60 to 150° C. for a time that substantially all epoxy groups react to form a polyamine core. Typically, the reaction time is in the range of 30 to 300 minutes. In the second reaction step, the polyamine core is suitably reacted with a polyester segment, typically a polyester segment having one carboxylic acid group. The polyamine core and the polyester segment are suitably reacted by mixing and heating to a temperature in the range of 60 to 150° C., preferably 80 to 140° C. The suitable reaction time is in the range of 30 minutes to 300 minutes. The polyester segment is prepared according to generally known methods as described above. The preparation of suitable polymers for the composition according to the present invention is also described in the Examples section of US 9574121 B2.

[0048] The composition of the present invention further comprises a conductive carbon-based material. A carbon-based material is a material consisting of 90 to 100% by weight of carbon. In order to be used in the field of electrode manufacturing of a battery pack, a conductive carbon-based material is selected. Examples of suitable conductive carbon-based materials include carbon black, carbon nanotubes, graphite, carbon fiber, graphene, fullerene and mixtures thereof. Preferred carbon-based materials are carbon black, graphene and carbon nanotubes.

[0049] Typically, the weight ratio of polymer a) to conductive carbon-based material b) in the composition of the present invention is in the range of 70:100 to 3:100, preferably in the range of 50:100 to 5:100, most preferably in the range of 30:100 to 7:100.

[0050] The composition of the present invention is intended for use in the manufacture of electrodes for rechargeable batteries. Thus, the composition suitably comprises a cathode active material for a rechargeable battery.

[0051] In the cathode of a lithium-ion rechargeable battery, a lithium-containing transition metal oxide or lithium metal phosphate, such as LiFePO4, is generally used as a cathode active material, preferably an oxide mainly containing lithium and at least one transition metal element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Mo and W, which is a compound with a molar ratio of lithium to the transition metal element of 0.3 to 2.2. More preferably, an oxide mainly containing lithium and at least one transition metal element selected from V, Cr, Mn, Fe, Co and Ni is used, which is a compound with a molar ratio of lithium to the transition metal of 0.3 to 2.2. It should be noted that Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, B, etc. may be contained in a range of less than 30 mol% relative to the transition metal mainly present. Among the active materials mentioned above, at least one having the general formula Li x MO2 (M represents at least one of Co, Ni, Fe and Mn, and x is 0 to 1.2) or Li y A spinel structure material represented by N2O4 (N contains at least Mn, and y is 0 to 2).

[0052] Furthermore, as the cathode active material, at least one each including Li y M a D 1-a O2 material (M represents at least one of Co, Ni, Fe and Mn, D represents at least one of Co, Ni, Fe, Mn, Al, Zn, Cu, Mo, Ag, W, Ga, In, Sn, Pb, Sb, Sr, B and P, provided that the element corresponding to M is not included, y = 0 to 1.2, and a = 0.5 to 1) and each having a Li z (N b E 1-b )2O4 (N represents Mn, E represents at least one of Co, Ni, Fe, Mn, Al, Zn, Cu, Mo, Ag, W, Ga, In, Sn, Pb, Sb, Sr, B and P, b = 1 to 0.2, and z = 0 to 2) represents a spinel structure material.

[0053] Specifically, take Li x CoO2、Li x NiO2、Li x MnO2、Li x Co a Ni 1-a O2、Li x Co b V 1-b O z , Li x Co b Fe 1-bO2、Li x Mn2O4、Li x Mn c Co 2-c O4、Li x Mn c Ni 2-c O4、Li x Mn c V 2-c O4 and Li x Mn c Fe 2-c O4 (wherein x=0.02 to 1.2, a=0.1 to 0.9, b=0.8 to 0.98, c=1.6 to 1.96, and z=2.01 to 2.3). As the most preferred lithium-containing transition metal oxide, Li x CoO2、Li x NiO2、Li x MnO2、Li x Co a Ni 1-a O2、Li x Mn2O4 and Li x Co b V 1-b O z (x=0.02 to 1.2, a=0.1 to 0.9, b=0.9 to 0.98 and z=2.01 to 2.3) It should be noted that the value of x may increase and decrease with charging and discharging.

[0054] Although there is no particular limitation on the average particle size of the cathode active material, the particle size is preferably 0.1 to 50 μm. Preferably, the volume of particles of 0.5 to 30 μm is 95% or more. More preferably, the volume occupied by a particle group with a particle size of 3 μm or less is 18% or less of the total volume, and the volume occupied by a particle group of 15 μm or more and 25 μm or less is 18% or less of the total volume.

[0055] In a preferred embodiment, the cathode active material comprises at least one of lithium nickel-cobalt-aluminum oxide and lithium nickel-manganese-cobalt oxide.

[0056] The composition of the present invention is suitably a liquid or paste at a temperature of 20° C. This facilitates the preparation of an electrode from the composition. In order to make the composition liquid or paste-like, the composition preferably further comprises at least one organic solvent in an amount of 10 to 90% by weight based on the total weight of the composition.

[0057] Typically, the organic solvent is selected to be able to dissolve the polymer or oligomer component of the composition.The organic solvent may also comprise more than one type of organic solvent, such as a mixture of two or more types of solvents. Examples of suitable solvents include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene, toluene and fluorobenzene; or carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents such as ethanol and isopropanol; nitriles such as R—CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may include a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane may be used as the organic solvent. Examples of other suitable solvents include aprotic dipolar solvents such as dimethyl sulfoxide, dimethylformamide or N-methylpyrrolidone, or other solvents containing amide groups. In the case of using water as a solvent, it may be preferred to further include a thickener. The amount of solvent is adjusted to obtain a viscosity that allows the paste to be easily applied to a collector.

[0058] Typically, the solvent is present in the composition of the present invention in an amount of 10 to 90 wt %, preferably 20 to 80 wt %, based on the total weight of the composition.

[0059] In a further preferred embodiment, the composition further comprises a polymer binder. The binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Examples of binders include known binders, such as: fluorine-based polymers, such as polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymers and polytetrafluoroethylene; rubber-based binders, such as styrene-butadiene rubber (SBR), ethylene-propylene-diene monomer rubber (EPDM), sulfonated EPDM and fluororubber; polyethylene; polypropylene; polyvinyl alcohol; polyvinyl pyrrolidone, polyacrylonitrile; carboxymethyl cellulose (CMC); starch; hydroxypropyl cellulose; regenerated cellulose; and binders based on polyacrylates. If necessary, the binder can be used in the form of an aqueous dispersion.

[0060] The binder is suitably used in an amount of 1.0 to 50.0 parts by mass relative to 100 parts by mass of the nonvolatile material of the composition, and particularly, the amount is preferably about 1.0 to 20.0, more preferably 1.0 to 10.0 parts by mass of the nonvolatile material of the composition.

[0061] The composition of the invention is very suitable for preparing an electrode for a rechargeable battery. Therefore, the present invention also relates to the use of the composition of the invention for preparing an electrode for a rechargeable battery, and a method for preparing an electrode for a rechargeable battery, wherein the composition according to the invention is used for preparing a battery electrode. Preferably, the electrode is a cathode.

[0062] The composition of the present invention can be prepared by mixing the components to prepare a paste or slurry, for example, by kneading. A solvent can be used during kneading. Examples of solvents include known solvents such as dimethylformamide and isopropanol; in the case of fluorine-based polymers, toluene and N-methylpyrrolidone; in the case of SBR, water. In the case of an adhesive using water as a solvent, a thickener is preferably used in the composition. The amount of the solvent is adjusted to obtain a viscosity that allows the paste to be easily applied to the current collector.

[0063] The electrode can be formed by molding the electrode paste mentioned above. For example, the electrode is obtained by applying the electrode paste to a current collector, followed by drying and pressure molding.

[0064] Examples of current collectors include foils and meshes of aluminum, nickel, copper, stainless steel, etc. The coating thickness of the paste is generally 40 to 200 μm. There is no particular limitation on the paste coating method, and one example of the coating method includes a method involving coating with a doctor blade or a rod coater, followed by molding by roll pressing, etc.

[0065] Examples of pressure molding include roll pressure molding, compression molding, etc. The pressure used for pressure molding is preferably about 1 to 3 t / cm 2 As the electrode density increases, the battery capacity per unit volume generally increases. However, if the electrode density increases too much, the cycle characteristics generally deteriorate. If the electrode paste in a preferred embodiment of the present invention is used, the cycle characteristics deteriorate little even if the electrode density is increased. Generally, the electrode density is between 1.0 and 4.0 g / cm 3 In some embodiments, the electrode density of the cathode is between 2.0 and 3.5 g / cm 3 The density of the anode is between 1.2 and 2.0 g / cm 3 within the range.

[0066] The invention further relates to a battery electrode comprising the composition according to the invention, and a rechargeable battery comprising said electrode.The expression "battery" encompasses a single electrochemical cell containing electrodes, separator and electrolyte, as well as a group of cells or a battery assembly.

[0067] In a lithium ion rechargeable battery, a separator may be provided between a cathode and an anode. Examples of the separator include nonwoven fabrics, cloths, and microporous films, each mainly containing polyolefins such as polyethylene and polypropylene, combinations thereof, and the like.

[0068] The invention further relates to the use of a polymer in the preparation of a composition for preparing an electrode of a rechargeable battery, the polymer having

[0069] i) a polyamine core comprising a plurality of amine groups and comprising a structure of formula (I)

[0070]

[0071] Where R 1 is part of the H or polyamine nucleus, R 2 is H or an organic group, R 3 is H or an organic group, provided that R 2 and R 3 At least one is H,

[0072] ii) Multiple polyester segments linked to a polyamine core via ionic bonds. Example

[0073] Polyester 1

[0074] 140.00 g (0.67 mol) of lauric acid and 797.78 g (6.99 mol) of ε-caprolactone were added to a 4-necked flask and heated to 90° C. 0.47 g of tetra-n-butyl zirconate was added. The reaction mixture was kept at 90° C. for a period of 4 hours, then heated to 190° C. and kept at this temperature for 1 hour. Thereafter, the material was cooled to room temperature. The theoretical molecular weight of the polyester was 1400 g / mol.

[0075] Polyester 2

[0076] 101.55 g (0.51 mol) of lauric acid and 927.96 g (8.13 mol) of ε-caprolactone were added to a 4-necked flask and heated to 90° C. 0.47 g of tetra-n-butyl zirconate was added. The reaction mixture was kept at 90° C. for a period of 4 hours, then heated to 190° C. and kept at this temperature for 1 hour. Thereafter, the material was cooled to room temperature. The theoretical molecular weight of the polyester was 2028 g / mol.

[0077] Polyester 3

[0078] 101.55 g (0.51 mol) of lauric acid, 203.35 g (2.04 mol) of γ-valerolactone and 694.60 g (6.09 mol) of ε-caprolactone were added to a 4-necked flask and heated to 90°C. Then 0.47 g of tetra-n-butyl zirconate was added. The reaction mixture was kept at 90°C for a period of 4 hours, then heated to 190°C and kept at this temperature for 1 hour. Thereafter, the material was cooled to room temperature. The theoretical molecular weight of the polyester was 1970 g / mol.

[0079] Preparation of polymers having a polyamine core and multiple polyester segments

[0080] Raw materials used:

[0081] PEI 1 = Polyethyleneimine 10.000 g / mol, Epomin SP200, Nippon Shokubai PEI 2 = Polyethyleneimine 2000 g / mol, Lupasol PR 8515, BASF PEI 3 = Polyethyleneimine 1300 g / mol, Lupasol G 20, BASF

[0082] Comparative Example 1

[0083] 7.0 g (0.0007 mol) of PEI 1 and 93.0 g (0.0694 mol) of polyester 1 were added to a 4-necked flask and heated to 150°C and kept at this temperature for 5 hours, then the reaction mixture was cooled to room temperature. The acid value was 24.1 mg KOH / g. This corresponds to 66.5% of the polyester segments being ionically linked to the polyamine core.

[0084] Example 1

[0085] 7.0 g (0.0007 mol) of PEI 1 was added to a 4-necked flask and heated to 110°C. 0.9 g (0.0056 mol) of cresyl glycidyl ether was added and homogenized. The mixture was heated to 130°C and 93.00 g (0.0694 mol) of polyester 1 was added. The mixture was kept at this temperature for 3 hours and then the reaction mixture was cooled to room temperature. The acid number was 31.1 mgKOH / g. This corresponds to 87.6% of the polyester segments being ionically bonded to the polyamine core.

[0086] Comparative Example 2

[0087] 24.00 g (0.01201 mol) of PEI 2 was added to a 4-necked flask and heated to 80°C. 72.00 g (0.03599 mol) of polyester 2 and 24.00 g (0.01201 mol) of polyester 3 were added. The mixture was heated to 120°C and kept at this temperature for 3 hours, and then the reaction mixture was cooled to room temperature. The acid value was 22.4 mg KOH / g. This corresponds to 87.6% of the polyester segments being ionically linked to the polyamine core.

[0088] Example 2

[0089] 8.39 g (0.0042 mol) of PEI 2 were added to a 4-necked flask and heated to 110°C. 11.62 g (0.05095 mol) of neodecanoic acid glycidyl ester were slowly added and homogenized over a period of 0.5 hours. Then 25.17 g (0.01258 mol) of polyester 2 and 8.39 g (0.0042 mol) of polyester 3 were added. The mixture was heated to 130°C and maintained at this temperature for 3 hours, and then the reaction mixture was cooled to room temperature. The acid number was 16.3 mg KOH / g. This corresponds to 92.6% of the polyester segments being ionically bonded to the polyamine core.

[0090] Example 3

[0091] 7.00 g (0.0007 mol) of PEI 1 was added to a 4-necked flask and heated to 110°C. 2.52 g (0.0111 mol) of neodecanoic acid glycidyl ester was added and homogenized for 0.5 h. The mixture was heated to 130°C and 93.00 g (0.0694 mol) of polyester 1 was added. The mixture was kept at 130°C for 3 hours and then the reaction mixture was cooled to room temperature. The acid number was 32.8 mg KOH / g. This corresponds to 86.3% of the polyester segments being ionically bonded to the polyamine core.

[0092] Example 4

[0093] 7.0 g (0.0007 mol) of PEI 1 was added to a 4-necked flask and heated to 110°C. 0.63 g (0.0028 mol) of neodecanoic acid glycidyl ester was added and homogenized for 0.5 h. The mixture was heated to 130°C and 93.00 g (0.0694 mol) of polyester 1 was added. The mixture was kept at 130°C for 3 hours and then the reaction mixture was cooled to room temperature. The acid number was 33.0 mg KOH / g. This corresponds to 85.3% of the polyester segments being ionically bonded to the polyamine core.

[0094] Example 5

[0095] 7.0 g (0.0007 mol) of PEI 1 was added to a 4-necked flask and heated to 110°C. 0.93 g (0.0055 mol) of ethylhexyl glycidyl ether was added and homogenized for 0.5 h. The mixture was heated to 130°C and 93.00 g (0.0694 mol) of polyester 1 was added. The mixture was kept at 130°C for 3 hours and then the reaction mixture was cooled to room temperature. The acid number was 33.0 mg KOH / g. This corresponds to 85.5% of the polyester segments being ionically bonded to the polyamine core.

[0096] Example 6

[0097] 7.0 g (0.0007 mol) of PEI 1 was added to a 4-necked flask and heated to 110°C. 0.91 g (0.0055 mol) of cresyl glycidyl ether was added and homogenized for 0.5 h. The mixture was heated to 130°C and 93.00 g (0.0694 mol) of polyester 1 was added. The mixture was kept at 130°C for 3 hours and then the reaction mixture was cooled to room temperature. The acid number was 33.0 mg KOH / g. This corresponds to 85.7% of the polyester segments being ionically bonded to the polyamine core.

[0098] Example 7

[0099] 12.2 g (0.0925 mol) of PEI 3 was added to a 4-necked flask and heated to 110°C. 16.67 g (0.0731 mol) of glycidyl neodecanoate was added and homogenized for 0.5 hours. 34.81 g (0.0174 mol) of polyester 2 and 11.6 g (0.0058 mol) of polyester 3 were added. The mixture was heated to 130°C and maintained at this temperature for 3 hours, and then the reaction mixture was cooled to room temperature.

[0100] Comparative Example 3

[0101] 12.2 g (0.0925 mol) of PEI 3 were added to a 4-necked flask and heated to 80°C. 34.81 g (0.0174 mol) of polyester 2 and 11.6 g (0.0058 mol) of polyester 3 were added. The mixture was heated to 130°C and kept at this temperature for 3 hours, and then the reaction mixture was cooled to room temperature. The acid number was 18.6 mg KOH / g. This corresponds to 84.1% of the polyester segments being ionically linked to the polyamine core.

[0102] Example 8

[0103] 12.55 g (0.00125 mol) of PEI 1 was added to a 4-necked flask and heated to 110°C. 16.13 g (0.0708 mol) of glycidyl neodecanoate was added and homogenized for 0.5 hours. 33.69 g (0.0168 mol) of polyester 2 and 11.22 g (0.0056 mol) of polyester 3 were added. The mixture was heated to 130°C and maintained at this temperature for 3 hours, and then the reaction mixture was cooled to room temperature.

[0104] Comparative Example 4

[0105] 12.55 g (0.00125 mol) of PEI 1 was added to a 4-necked flask and heated to 80° C. 33.69 g (0.0171 mol) of polyester 2 and 11.22 g (0.0056 mol) of polyester 3 were added. The mixture was heated to 130° C. and maintained at this temperature for 3 hours, and then the reaction mixture was cooled to room temperature.

[0106] Application test

[0107] In a 250 ml polypropylene cup, 0.3 g of dispersant was homogenized in 16.7 g of N-methylpyrrolidone. Next, 3 g of conductive carbon black (IMERYS C-Nergy SUPER C 65) and 40 g of glass beads (0.75 mm) were added. Dispersion was performed at 1400 rpm using a Hauschild SpeedMixer DAC 400 for 9 minutes, and then the glass beads were screened out. Finally, the slurry was evaluated by measuring the viscosity at 23 ° C on an Anton Paar MCR 102 with a cone / plate geometry (a cone with a diameter of 25 mm and an angle of 1 °).

[0108] The results of the viscosity measurements are summarized in the table below.

[0109]

[0110]

[0111] Tests conducted with Comparative Examples 1 and 2 resulted in slurries with such high viscosities that it was not possible to screen out the glass beads. Thus, these comparative dispersants resulted in slurries with unacceptably high viscosities. Comparative Example 3 also resulted in slurries with unacceptably high viscosities. The slurries prepared with the examples according to the invention all had significantly lower viscosities than the comparative examples. This conclusion applies to a variety of shear rates.

[0112] In a 250 ml polypropylene cup, 0.3 g of dispersant was homogenized in 16.7 g of NMP. Next, 3 g of conductive carbon black (Denka Black Li 400) and 40 g of glass beads (0.75 mm) were added. A Hauschild SpeedMixer DAC 400 was used to disperse for 9 minutes at 1400 rpm, and then the glass beads were screened out. Finally, the slurry was evaluated by measuring the viscosity at 23 ° C with a cone / plate geometry (cone with a 25 mm diameter and a 1 ° angle) on an Anton Paar MCR 102.

[0113] The results of the viscosity measurements are summarized in the table below.

[0114]

[0115] The test with Comparative Example 1 resulted in a slurry with such a high viscosity that it was impossible to screen out the glass beads. Thus, this comparative dispersant resulted in a slurry with an unacceptably high viscosity. Comparative Example 4 also resulted in a slurry with an unacceptably high viscosity. The slurries prepared with the examples according to the invention all had a significantly lower viscosity than the comparative examples. This conclusion applies to a variety of shear rates.

Claims

1. A composition comprising a) a polymer having i) a polyamine core comprising a plurality of amine groups and comprising a structure of formula (I) Where R 1 is part of the H or polyamine nucleus, R 2 is H or an organic group, R 3 is H or an organic group, provided that R 2 and R 3 At least one is H, ii) a plurality of polyester segments connected via ionic bonds to a polyamine core, and b) Conductive carbon-based materials The weight ratio of the polymer a) to the conductive carbon-based material b) in the composition of the present invention is in the range of 70:100 to 3:

100.

2. The composition of claim 1, wherein the polyamine core is polyethyleneimine.

3. A composition according to claim 1 or 2, wherein the polyamine core has a weight average molecular weight in the range of 300 to 25000 g / mol.

4. A composition according to any one of the preceding claims, wherein R 2 and R 3 Independently selected from a hydrocarbon group, an organic group comprising an ether group, and an organic group comprising an ester group.

5. A composition according to any preceding claim, wherein the polymer further comprises polyester segments linked to a polyamine core via amide groups.

6. The composition of claim 5, wherein 10 to 40% of the polyester segments are linked to the polyamine core via amide groups, and wherein 90 to 60% of the polyester segments are linked to the polyamine core via ionic bonds.

7. The composition according to any one of the preceding claims, wherein the polyester segment comprises a polyester of the formula -[-O-(CH2) n -C(=O)]-, wherein n is an integer in the range of 3 to 6.

8. The composition according to any one of the preceding claims, wherein the carbon-based material comprises at least one of carbon black, carbon nanotubes, graphite, carbon fibers, graphene and fullerenes.

9. The composition according to any one of the preceding claims, wherein the weight ratio of polymer a) to conductive carbon-based material b) in the composition of the invention is in the range of 50:100 to 5:

100.

10. The composition of any preceding claim, wherein the composition further comprises a cathode active material for a rechargeable battery.

11. The composition of claim 10, wherein the cathode active material comprises at least one of lithium nickel-cobalt-aluminum oxide and lithium nickel-manganese-cobalt oxide.

12. The composition according to any one of the preceding claims, wherein the composition further comprises at least one organic solvent in an amount of 10 to 90 wt. %, based on the total weight of the composition.

13. The composition according to any one of the preceding claims, wherein the composition further comprises a polymer binder which is different from the polymer comprised in the composition according to any one of the preceding claims 1 to 12.

14. Use of a composition according to any one of the preceding claims for the preparation of an electrode for a rechargeable battery.

15. A method for preparing a rechargeable battery electrode, wherein the battery electrode is prepared using a composition according to any one of the preceding claims 1 to 13.

16. A battery electrode comprising the composition according to any one of the preceding claims 1 to 13.

17. A rechargeable battery comprising the electrode according to claim 16.

18. Use of a polymer in the preparation of a composition for preparing an electrode of a rechargeable battery, the polymer having i) a polyamine core comprising a plurality of amine groups and comprising a structure of formula (I) Where R 1 is part of the H or polyamine nucleus, R 2 is H or an organic group, R 3 is H or an organic group, provided that R 2 and R 3 At least one is H, ii) Multiple polyester segments linked to a polyamine core via ionic bonds.

Citation Information

Patent Citations

  • Amine adducts based on epoxide compounds

    US9574121B2

  • dispersant

    WO2021028519A1